Weichselian history of the Fennoscandian ice sheet in southern Sweden and the southwestern Baltic Basin. (24th October 2013) - Anjar, Johanna; Adrielsson, Lena; Larsen, Nicolaj Krog; Möller, Per; Barth, Kilian
<x xml:space="preserve">Abstract</x> This study presents the Weichselian stratigraphy on Kriegers Flak in the southwestern Baltic Sea, and correlates it to new sections in southernmost Sweden and to previously published stratigraphic sequences from SW Skåne. A total of four Weichselian advances are identified based on our correlations. The oldest till, observed only on Kriegers Flak, is dated to the Early or Middle Weichselian and tentatively correlated to the Ristinge advance, previously identified in Denmark. It is overlain by three interstadial sediment units, starting with brackish clay and followed by terrestrial and lacustrine deposits, which have been dated to 42–36 ka, and finally by glaciolacustrine clay dated to 28.5–26 ka. After 30 ka, the Fennoscandian ice sheet advanced through the Baltic Basin and into the coastal areas of southernmost Sweden where the Allarp Till was deposited, followed by a deglaciation sequence. The uppermost tills, the Dalby Till and the Lund till, were deposited during the LGM advance and the subsequent re‐advances through the Baltic Basin. Based on the new evidence it has been possible to identify and date a Middle and Late Weichselian till succession in southern Sweden and provide a strong correlation to the established glacial stratigraphies in Sweden and Denmark.